Pyridinedicarboxylic Acid Derivatives of Dichlorobis(cyclopentadienyl)titanium(IV) - Satish C. Dixit; Rohit K. Singh (E-Journal of Chemistry)
Reactions of dichlorobis(cyclopentadienyl)titanium(IV) with pyridine dicarboxylic acids viz. quinolinic acid (QAH2), 2,4-pyridine dicarboxylic acid (PAH2), isocinchomeronic acid (IAH2), cinchomeronic acid (CAH2) and dinicotinic acid (DAH2) were carried out in different stoichiometric ratios. Complexes of the type Cp2Ti(QAH)Cl, Cp2Ti(QAH)2, Cp2Ti(PAH)Cl, Cp2Ti(PAH)2, Cp2Ti(IAH)Cl, Cp2Ti(IAH)2, Cp2Ti(CAH)Cl, Cp2Ti(CAH)2, Cp2Ti(DAH)Cl and Cp2Ti(DAH)2 were obtained. These new complexes were characterized on the basis of their elemental analyses, electrical conductance, magnetic moment and spectral data.